2018
DOI: 10.1016/s2213-2600(18)30289-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambulatory oxygen on quality of life for patients with fibrotic lung disease (AmbOx): a prospective, open-label, mixed-method, crossover randomised controlled trial

Abstract: UK National Institute for Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 41 publications
(25 reference statements)
1
110
0
9
Order By: Relevance
“…King's Brief Interstitial Lung Disease questionnaire (K-BILD) was developed as a HRQL instrument for patients with ILD [9] and has recently been validated in IPF [10]. Even though K-BILD is used in clinical trials [11,12], responsiveness and MCID have not yet been sufficiently determined [13,14]. Validation of an instrument is an iterative process increasing robustness by evaluation in different cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…King's Brief Interstitial Lung Disease questionnaire (K-BILD) was developed as a HRQL instrument for patients with ILD [9] and has recently been validated in IPF [10]. Even though K-BILD is used in clinical trials [11,12], responsiveness and MCID have not yet been sufficiently determined [13,14]. Validation of an instrument is an iterative process increasing robustness by evaluation in different cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated reduced dyspnoea, improved capacity and decreased desaturation degree in patients receiving oxygen during exercise, with high oxygen concentrations in inspiratory air (FiO 2 > 0.50) [338]. In another randomised, cross-over, two-week, prospective trial comparing the effects of two-week oxygen therapy using a portable oxygen source with a period without oxygen therapy in IPF patients with latent hypoxaemic respiratory failure, oxygen therapy was found to have a beneficial effect on the quality of life [339]. Oxygen therapy using a portable oxygen source does not reduce exercise-induced increase in pulmonary artery pressure [340].…”
Section: Question 23 Should Oxygen Be Used During Exercise In Ipf Pamentioning
confidence: 99%
“…It should, however, be recommended to LTOT patients who are still involved in outdoor activities as well as patients participating in pulmonary rehabilitation programmes if improved physical capacity has been demonstrated as a result of using a portable oxygen source [341]. The AmbOx trial results suggest that, compared with lack of oxygen therapy, the use of oxygen from portable sources during exercise decreases desaturation and dyspnoea during exercise and also improves the quality of life in patients with ILDs, without resting hypoxaemia [339]. When recommending the use of oxygen from portable sources, one should remember the costs and physical strain associated with carrying or pulling an oxygen-delivering device as well as the need for frequent refilling [342].…”
Section: Commentarymentioning
confidence: 99%
“…The only published randomised prospective trial in patients with ILD, evaluating longer-term effects of AOT, delivered via compressed oxygen cylinders, is the Ambulatory Oxygen in Fibrotic Lung Disease (AmbOx) trial [69]. The AmbOx trial was a multicentre randomised controlled crossover trial in the UK comparing the effects of AOT with no AOT during activities in patients with fibrotic ILD and isolated exertional desaturation.…”
Section: Ambulatory Oxygen Therapy In Copd and Ildmentioning
confidence: 99%